Cultivating achievement, respect, and empowerment (CARE) for African American girls in pre-K-12 settings : implications for access, equity and achievement - Larke, Patricia J.; Webb-Hasan, Gwendolyn; Young, Jemimah L. (Contemporary perspectives on access, equity, and achievement., 2016)
Chapters discuss issues impacting the education of African American girls and many of challenges that they encounter during their schooling experiences. The chapters were written by 24 authors including a school superintendent, university administrator and professors, classroom teacher, mother and a 10th grade African American student.The 20 chapters of the book are organized into four sections. Section one introduces the book and provides critical perspectives. Section Two focuses on Curriculum and instruction. Section Three shares information from significant stakeholders while the last section includes other schooling experiences and ends with a powerful poem by a tenth grade African American girl, entitled 'Proud.' The forward of the book, written by a Japanese American scholar, Valerie Pang, denotes the urgency of the book noting that the book 'warms the heart.' The book ends with an epilogue, written by an African American scholar, Tyrone Howard, who has a vested interest in African American males. He shares commanding interest in this scholarship, because what happens to African American females, impacts African American males and the entire African American community.